Caught : Montreal's Modern Girls and the Law, 1869-1945 - Myers, Tamara, 1964- (Book collections on Project MUSE., 2006)
Caught exposes the attempts made by the juvenile justice system of the day to curb modern attitudes and behaviour; at the same time, it reveals the changing patterns of social and family interaction among adolescent girls.